Efficacy of steroid injection versus physiotherapy treatment in work related trigger finger - Mustapha, Mohd Farid; Ismail, Raffael; Kassim, KM; Singh, ASJ; Khalid, Kamarul Ariffin (Kulliyyah of Allied Health Sciences, IIUM, 2019)
Stenosing tenosynovitis or trigger finger is a common problem among patients seeking treatment in the orthopaedic clinic. Multiple approaches can be used to treat a patient with a trigger finger. This study to compare the functional outcome of steroid injection versus physiotherapy between service and professional workers with trigger finger. We use observational cohort study. Evaluating the functional outcome of treatment physiotherapy and steroid injection among professional and service workers for trigger finger grade I, II, and III. We also assess the recurrence of the affected finger. Malaysia Standard Classification of Occupation 2013 (MASCO) has been used to classify two working groups: professional and service worker. Michigan Hand Outcomes Questionnaire (MHQ) used for the finger assessment. The patient was observed with three separated visits; pre-treatment visits, six months and 12 months. The patient was divided into two groups of steroid injection and physiotherapy for evaluation of functional outcome and recurrence. The total number of patients recruited is 149 with 75 in the professional group and 74 in the service group. Out of the 149 patients, 80 were treated with physiotherapy and 69 were with steroid injection. There was no association between the occupation and the grading of trigger finger and the affected finger itself. Functional outcome using MHQ score for steroid group shows a good 12 months outcome (P values <0.01) comparing with physiotherapy group. Functional outcome in terms of physiotherapy was lower compared to steroid injection at six months and 12 months. The recurrence rate in physiotherapy was higher than in the steroid injection group. Single steroid injection had a better functional outcome after six months and 12 months post-intervention compared with physiotherapy. Physiotherapy treatment can be suggested to patients with grade 1, 2, and 3 of trigger finger who refused any steroid injection.